2018
DOI: 10.1016/j.bpj.2017.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of H-Bond Donor Lipids on Phosphatidylinositol-3,4,5-Trisphosphate Ionization and Clustering

Abstract: The phosphoinositide, phosphatidylinositol-3,4,5-trisphosphate (PI(3,4,5)P), is a key signaling lipid in the inner leaflet of the cell plasma membrane, regulating diverse signaling pathways including cell growth and migration. In this study we investigate the impact of the hydrogen-bond donor lipids phosphatidylethanolamine (PE) and phosphatidylinositol (PI) on the charge and phase behavior of PI(3,4,5)P. PE and PI can interact with PI(3,4,5)P through hydrogen-bond formation, leading to altered ionization beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 32 publications
3
22
0
Order By: Relevance
“…With this in mind, the P3 and P5 phosphate beads of our CG model of PI (3,4,5)P3 were set at charge -1.3 and the P4 bead was set at -1.4 to reflect this behavior. The slightly higher charge for the P4 phosphate is in agreement with experimental observations 82,83 .…”
Section: Phosphoinositide Parameterizationsupporting
confidence: 91%
See 1 more Smart Citation
“…With this in mind, the P3 and P5 phosphate beads of our CG model of PI (3,4,5)P3 were set at charge -1.3 and the P4 bead was set at -1.4 to reflect this behavior. The slightly higher charge for the P4 phosphate is in agreement with experimental observations 82,83 .…”
Section: Phosphoinositide Parameterizationsupporting
confidence: 91%
“…PI (3,4,5)P3, where the three phosphorylations are adjacent, is also a complex case. Its behavior is similar to that of the phosphatidylinositol bisphosphate lipids, with protons being shared between adjacent phosphates 82,83 . As such, the most common charge state at physiological pH, is to have 2 phosphate groups fully deprotonated, with the third phosphate group mono-protonated and sharing its last proton with the adjacent phosphate groups.…”
Section: Phosphoinositide Parameterizationmentioning
confidence: 73%
“…Lipid cooperativity (i.e., interaction with more than one lipid molecule and/or species) may also play a key role in the recruitment of PH domains to cell membranes (6,7). Furthermore, it is thought that nanoscale lipid clustering may play a key role in the interactions of membrane proteins with lipids (8,9), in turn influencing the avidity of recognition proteins for membranes (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…57 Graber et al also reported that when PE was included with PC/PI(3,4,5)P3 mixtures, there is a stepwise deprotonation of the phosphates that leads to a preference for hydrogen bonding between the primary amine of PE and the 3′-phosphate. 58 The SAXS studies carried out here on PC/PE/PI ternary mixture delineates PI’s role in determining lipid packing and hence structural ordering. However, there are no PI phosphates to interact with the PE primary amine in the mixtures in this report.…”
Section: Resultsmentioning
confidence: 92%
“…53,57 Alternatively, Graber et al reported that PE containing ternary mixtures caused hydrogen bonding between the primary amine of the PE and the PIP 3′- or 5′-phosphomonoester groups, and do not exhibit phase separation. 57,58 While it is clear that phase separation occurs in PC/PIP mixtures, even as low as 3 mol % PIP, 52 it is not clear if Amot “senses” a phase separation in the nonphosphorylated mixture. However, on the basis of the lipid affinity assays conducted by Heller et al, it was determined that the ACCH domain had a strong affinity for PI and PIP, and almost none for mixtures containing PIP2 and PIP3.…”
Section: Introductionmentioning
confidence: 99%